FRUIT MATURATION IN FOUR MUSCADINE GRAPE CULTIVARS IN PINHAIS, PR - SACHI, Adriana De Toni; BIASI, Luiz Antonio (Scientia Agraria, 2008)
The objective of this work was to evaluate fruit maturation of four muscatine grape cultivars to determine the harvest date for these cultivars. The experiment was performed from March to April 2007 at the Fruit Crop Section of the Canguiri Experimental Station, Federal University of Parana, in Pinhais, PR, Brazil. Grape berry maturation of two white (Dixie and Roanoke) and two red (Bontiful and Regale) muscadine cultivars were monitored from veraison to ripe berry. Five replications of five randomly selected clusters from each cultivar were collected once a week, for seven weeks. The analyzed variables were soluble solids (SS), pH, titratable acidity (TA) and SS/TA ratio. Dixie presented the highest SS, pH and SS/TA ratio and the lowest TA of the four tested cultivars during the whole maturation process. The red cultivars presented lower SS/TA ratio than the white ones. Dixie and Bontiful were the most precocious cultivars, reaching the harvest point 215 days after bud break. Regale and Roanoke could be harvested at end of April, 229 days after bud break.